2019
DOI: 10.3389/fmicb.2018.03334
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in the Alpaca Gastrointestinal Tract Vary With Diet and Body Site

Abstract: Gut -associated microbes (‘gut microbiota’) impact the nutrition of their hosts, especially in ruminants and pseudoruminants that consume high-cellulose diets. Examples include the pseudoruminant alpaca. To better understand how body site and diet influence the alpaca microbiota, we performed three 16S rRNA gene surveys. First, we surveyed the compartment 1 (C1), duodenum, jejunum, ileum, cecum, and large intestine (LI) of alpacas fed a grass hay (GH; tall fescue) or alfalfa hay (AH) diet for 30 days. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
9
1
2
Order By: Relevance
“…This observation is in agreement with a prior report in camels [ 34 ]. The relative abundance of Bacteroides in our study is however clearly smaller than observed in a study of alpacas fed different diets [ 13 ]. Similar to camelids, Firmicutes is the main bacterial phylum identified in the fecal microbiota of most equine studies to date, while fewer reports identified Bacteroidetes as the most abundant phylum in horses [ 42 ].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…This observation is in agreement with a prior report in camels [ 34 ]. The relative abundance of Bacteroides in our study is however clearly smaller than observed in a study of alpacas fed different diets [ 13 ]. Similar to camelids, Firmicutes is the main bacterial phylum identified in the fecal microbiota of most equine studies to date, while fewer reports identified Bacteroidetes as the most abundant phylum in horses [ 42 ].…”
Section: Discussioncontrasting
confidence: 98%
“…Forage-associated differences in microbial populations were primarily attributable to site-specific shifts in Bacteroidaceae, Prevotella and Actinobacteria. The dominant phyla (Firmicutes and Bacteroidetes [ 13 ]) identified in the analyses of alpacas were also found to be abundant in previous studies of ruminants and pseudoruminants, although most prior work was focused on C1 microbiota composition [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afirma que los camélidos no son rumiantes ni son una amenaza para la industria ganadera porque tienen una resistencia total a las enfermedades infecciosas y parasitarias de los rumiantes. Las fuentes revisadas han configurado a los camélidos como falsos rumiantes o pseudorumiantes (Vallenas et al, 1971;Fowler, 2010;Carroll et al, 2019); y sus seguidores, por lo general replican el mismo texto, negando el carácter rumiante de los camélidos, lo cual constituye un error de concepto que merece un análisis objetivo.…”
Section: Los Camélidos Son Animales Rumiantesunclassified
“…This pattern is very similar to the activity periods shown by the alpacas in our experiment. Alpacas are classified as pseudo-ruminants (having a three-compartment forestomach) [23] and therefore we might expect alpacas to share similar diurnal activity patterns as ruminant species, such as cattle and sheep that also have multi-compartment stomachs. These species are known to show a daily pattern of three to five peaks of grazing activity [24,25].…”
Section: Diurnal Activity Patternsmentioning
confidence: 99%